Etika Politik Kesultanan Melayu-Bima - Adib Misbachul Islam (Masyarakat Pernaskahan Nusantara, 2011)
The presence of scientific publications on ancient manuscripts can indeed provide important information regarding various events that occurred in the past. Therefore, the publication of the text edition of Jawharat al-Ma'arif by Haji Nur Hidayatullah al-Manshur Muhammad Syuja'uddin, a descendant of the Bima nobility, edited by Oman Fathurahman—and published together with Bo' Bumi Luma Rasanae (edited by Henri Chambert-Loir and Massir Q. Abdullah) and Ten Letters of Sultan Bima Abdul Hamid Muhammad Syah (edited by Suryadi)—is nothing less than the rediscovery of fragments of social, intellectual, and political history from the historical structure of the Bima Sultanate specifically and the Malay-Nusantara Sultanate in general.